Effect of exercise-based management on multidirectional instability of the glenohumeral joint: a pilot randomised controlled trial protocol. Issue 9 (12th September 2016) - Warby, Sarah A; Ford, Jon J; Hahne, Andrew J; Watson, Lyn; Balster, Simon; Lenssen, Ross; Pizzari, Tania
Abstract : Introduction: The most commonly recommended treatment for multidirectional instability (MDI) of the shoulder is exercise. Despite this recommendation, there is limited evidence to support the effectiveness of exercise. The aim of this paper is to describe a pilot randomised controlled trial comparing the effectiveness of 2 exercise programmes on outcomes of participants with MDI. Methods and analysis: Consenting participants between 12 and 35 years, with non-traumatic MDI will be randomly allocated to participate in either the Rockwood Instability programme or the Watson MDI programme. Both programmes involve 1 consultation per week for 12 weeks with a physiotherapist to prescribe and progress a home exercise programme. Outcomes will be assessed at baseline, 6, 12, 24 and 52 weeks. Primary outcome measures include the Melbourne Instability Shoulder Score and Western Ontario Shoulder Index. Secondary outcomes include scapular coordinates, scapular upward rotation angles, muscle strength, symptomatic onset, limiting factor and angle of limiting factor in abduction range, incidence of complete glenohumeral joint dislocation, global rating of change, satisfaction scores, the Orebro Musculoskeletal Pain Questionnaire, adverse events and compliance with the home exercise programme. Data will be analysed on intention-to-treat principles and a per protocol basis. Discussion: This trial will evaluate whether there are differences in outcomes between the Rockwood and the Watson MDI programmes for participants with MDI. Ethics and dissemination: Participant confidentiality will be maintained with publication of results. Ethics approval: Faculty of Health Sciences (FHEC12/201). Trial registration number: ACTRN12613001240730 ; Pre-results.